Aquário e centro de pesquisa da vida aquática amazônica - Melo, Giovanna Perin (Brasil, 2023)
The project of the Amazonian Aquarium and Research Center for Aquatic Life aims to create a space that promotes leisure, tourism, and scientific education, featuring exhibition areas for Amazonian fish, laboratories, and an outdoor leisure area. The project was developed based on case studies, bibliographic and iconographic research, as well as field research conducted on-site and in the surrounding area where the intervention will take place. The lack of appreciation by the local population towards biodiversity and the neglect were reasons that led to the choice of this theme. The scientific research to be conducted on-site will contribute to understanding the biology of the animals and the conservation of species, maintaining the balance of the ichthyofauna. Additionally, the exhibition of the animals will serve educational and research purposes, promoting local tourism and visits from schools and universities. Overall, the project aims not only to provide a space for leisure and tourism but also to educate the population about the importance of preserving aquatic life in the Amazon.